Role of food aid and assistance in addressing the double burden of malnutrition in Ghana: a qualitative policy analysis - Niisoja M Torto; Kelly D Brownell (BMJ Nutrition, Prevention & Health)
Background and aims In many low-income and middle-income countries, the double burden of malnutrition threatens public health and economic progress, urging a re-evaluation of the roles and responsibilities of nutrition actors, both traditional and non-traditional. This study examines the food aid and assistance activities of the United Nations World Food Programme (WFP)—one non-traditional actor in the double burden conversation—and the potential for these activities to reach beyond their traditional mandate on undernutrition to also address overweight and obesity in Ghana.Methods Information on WFP activities in Ghana from 2012 up through its planning into 2023 was extracted from 11 WFP planning, operations and evaluation documents. WFP activities were then judged against the WHO’s framework on the determinants of the double burden of malnutrition to determine their potential to address the double burden. Semistructured interviews were also conducted with 17 key informants in the global nutrition landscape to identify challenges that may complicate the role of WFP and other actors in addressing the double burden.Results The analysis demonstrates that WFP activities in Ghana can serve as a platform on which to address the double burden, particularly by targeting the food access, food systems and socioeconomic disadvantage determinants of the double burden. Actors’ uncertainty with what role WFP should play in addressing the double burden, insufficient government attention to malnutrition and poor data on overweight and obesity were identified as potential challenges that complicate addressing the double burden.Conclusion The findings suggest that integrating WFP as a partner in the effort to address the double burden in Ghana might help amplify progress. To better address the double burden, WFP might prioritise retrofitting existing activities rather than implementing new interventions.